Vitamin E Intake Attenuated the Association Between Elevated Blood Heavy Metal (Pb, Cd, and Hg) Concentrations and Diabetes Risk in Adults Aged 18–65 Years: Findings from 2007–2018 NHANES - Chenggang Yang; Shimiao Dai; Yutian Luo; Qingqing Lv; Junying Zhu; Aolin Yang; Zhan Shi; Ziyu Han; Ruirui Yu; Jialei Yang; Longjian Liu; Ji-Chang Zhou (Toxics)
The association between heavy metal exposure and diabetes is controversial and vitamin E (VE) may reduce diabetes risk. We aimed to examine the associations between blood heavy metals (BHMs) and diabetes risk and VE’s role in the relationship. From the 2007–2018 NHANES, 10,721 participants aged ≥ 18 were included for multiple statistical analyses, which revealed that BHMs and dietary VE intake were negatively associated with diabetes and fasting plasma glucose (FPG). The diabetes prevalence in each quartile (Q) of heavy metal exposure increased with age, but within age Q4, it generally decreased with exposure quartiles. Moreover, BHMs were positively associated with all-cause and diabetes-related mortalities with aging, which induced an age breakpoint of 65 years for age-stratified analyses on the associations between BHMs and diabetes risk. In those aged > 65, BHMs were negatively correlated with diabetes risk and its biomarkers; however, in adults aged 18–65, the correlation was positive. At higher VE intake levels, blood lead was associated with a lower diabetes risk and all three BHMs demonstrated lower FPG levels than those at lower VE intake levels. In conclusion, consuming sufficient VE and avoiding heavy metal exposure are highly recommended to reduce diabetes risk.